ANALISIS KETERAMPILAN GURU DALAM MENGADAKAN VARIASI PEMBELAJARAN DI TK NEGERI PEMBINA LUBUK PAKAM - Hani Eklesia Sidauruk; Isa Hidayati (ADIBA : JOURNAL OF EDUCATION, 2025)
This study aims to analyze teacher skills in implementing learning variations at the Pembina Lubuk Pakam State Kindergarten (TK Negeri Pembina). Learning variations are one of the important aspects in early childhood education, which can increase student motivation and involvement in the learning process. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that teachers at Pembina Lubuk Pakam State Kindergarten have implemented various methods and strategies in implementing learning variations, such as the use of diverse media, changes in voice intonation, and the implementation of interactive and creative activities. However, there are several challenges faced, such as limited resources and facilities that affect the implementation of learning variations optimally. This study is expected to contribute to the development of teaching practices in kindergartens, as well as being a reference for managers in improving the quality of early childhood education.